VD_FINDINFO Jug / 2017 / 206 vom 27. Mai 2016 - VD Tribunal cantonal (2016)
ADMINISTRATION DES PREUVES, GESTION DÉLOYALE, FAUX MATÉRIEL DANS LES TITRES, CRÉANCE | 158 ch. 1 al. 1 CP, 251 ch. 1 CP, 71 CP, 10 CPP (CH), 139 CPP (CH), 398 al. 3 let. b CPP (CH)